Towards a Theory of State Visibility: Race, Poverty, and Equal Protection - Bridges, Kiara M. (Columbia Journal of Gender and Law, 2020)
In the state of New York, uninsured pregnant women with incomes falling below 200% of the federal poverty line are eligible to enroll in the Prenatal Care Assistance Program (“PCAP”), a Medicaid program that pays the prenatal healthcare expenses of women who meet the program’s qualifications. The aims of PCAP/Medicaid are laudable; it was passed in the late 1980’s with the goal of lowering the state’s high rate of infant mortality as well as the number of infants born with low birthweight. In order to justify the spending of state and federal monies on the program, legislators looked to studies that “documented the correlation between infant mortality and neurological abnormalities on the one hand, and low birthweight and premature birth on the other-conditions ameliorated by proper care throughout pregnancy, which can be costly.” Although the infant mortality rate in New York has decreased more than thirty percent over the last decade, New York State appears to remain committed to “improving the health of under- served women, infants and children through improved access to and enhanced utilization of perinatal and prenatal care and related services.” Consequently, it continues to provide generous funding to PCAP.